Innovation Opportunities in Organic Pineapple Production in Uganda - Nyamwaro, Sospeter O.; Tenywa, Moses M.; Kalibwani, Rebecca; Mugabo, Josaphat; Buruchara, Robin; Oluwole, Fatunbi (FARA Research Reports, 2018)
Pineapple is an important horticultural crop grown in many tropical countries as a major source of income. It is also consumed as fresh and dried fruit and has been found to have high nutritional and medicinal value. In Uganda, organic pineapple production is practiced as part of organic agriculture (OA) systems that have been found to be particularly suitable for small-scale farmers. The purpose of this research was to conduct a rapid organic pineapple VCA toward identifying innovation opportunities to boost the organic pineapple production and marketing in Uganda. Uganda is leading in Africa with the largest organic area (240,197ha) and highest number of organic producers (190,552), courtesy of NOGAMU, which has been instrumental in organic farming certification in Uganda. Pineapples are produced exclusively as a small-holder crop, either as sole crop or intercropped with other crops such as bananas in a given Ugandan farming system. Organic pineapple production in Uganda is faced with many constraints including lack of national policy to support pineapple production, costly certification, and low soil fertility. Pineapple VCA conducted at the Ntungamo Organic Pineapple IP show that the chain starts with input supply of suckers to small-holder IP farmers as the main players in production and marketing to various actors in local and urban markets. Innovation opportunities exist in Uganda that can boost pineapple VC for enhanced socioeconomic gains. The identified opportunities among others include increasing farm level production, provision of affordable certification for organic producers, acquisition of advanced solar driers, and introduction of small scale pineapple processing.
Keywords: Innovation opportunities; Organic pineapple; Innovation Platform